5x+x-8=5x+3

Simple and best practice solution for 5x+x-8=5x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+x-8=5x+3 equation:


Simplifying
5x + x + -8 = 5x + 3

Reorder the terms:
-8 + 5x + x = 5x + 3

Combine like terms: 5x + x = 6x
-8 + 6x = 5x + 3

Reorder the terms:
-8 + 6x = 3 + 5x

Solving
-8 + 6x = 3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-8 + 6x + -5x = 3 + 5x + -5x

Combine like terms: 6x + -5x = 1x
-8 + 1x = 3 + 5x + -5x

Combine like terms: 5x + -5x = 0
-8 + 1x = 3 + 0
-8 + 1x = 3

Add '8' to each side of the equation.
-8 + 8 + 1x = 3 + 8

Combine like terms: -8 + 8 = 0
0 + 1x = 3 + 8
1x = 3 + 8

Combine like terms: 3 + 8 = 11
1x = 11

Divide each side by '1'.
x = 11

Simplifying
x = 11

See similar equations:

| 18u^9w^9-24u^2w^4y^3= | | 3log(x)=5 | | y^2+4y-21= | | 75=5-7H | | 3-a=4a+19 | | 3K+11=2 | | 27=1+0.333333333x | | 49-m^2= | | (x-5)(x+3)=-15 | | -3x^2-42x-145=0 | | 14y^2+33y-5=0 | | -5z(z-6)(z+9)=0 | | (3x+4)-6(2x-6)=4x-16 | | 140+2x=1250 | | 1.8T=-72 | | 2x-140=1250 | | 6(3-h)=8h-10 | | 140-2x=1250 | | 9x+2=-7x-126 | | 0.20x+0.05(10-x)=0.10(32) | | 33=N+37 | | d^2-3d=6 | | (2m-5)x^2+mx+7=0 | | -16-p+12=26 | | 45xy-72zw=0 | | 17+2.66=30 | | z+31=26 | | cos(2x+1)=.3 | | cos(2x+1)=5 | | 3.5=x-9.9 | | 2(8)-3(5)+9= | | 3x^2+5=4x+4 |

Equations solver categories